The news media - Parks, Peggy J. 1951- (San Diego, Calif. Lucent Books, 2002)
Covers the various positions available in the field of print and broadcast journalism, discussing qualifications, training, job opportunities, and technological advances.
1. Reporters -- 2. Photojournalists -- 3. Television anchors -- 4. Broadcast producers -- 5. Radio announcers.
Includes bibliographical references and index.
Keywords: Journalism -- Vocational guidance -- Juvenile literature; Journalism -- Vocational guidance; Vocational guidance